Strategi Harga Dan Kualitas Pelayanan Pada Penjual Bakso Terhadap Kepuasan Pelanggan (UMKM Bakso Pakde Universitas Bhayangkara) - Dian Sudiantini; Faidlullah Mahfudz; Muhammad Zaky; Rizka Amalia Putri; Sunia Hatina (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
In Indonesia, small and medium-sized businesses (SMBs) in the food and drink industry are seeing unprecedented expansion. Lots of MSMEs are experiencing this as they try to win over consumers. With competition heating up in the food stall industry, the research focuses heavily on what makes customers happy. A food stand may increase customer satisfaction by focusing on three areas: price, service, and product quality. Setting reasonable prices, giving outstanding service, and delivering high-quality goods are all ways to make customers happy at the food stand. Satisfied customers will be more likely to return to the store. The sales income of Bakso Pakde has recently seen significant adjustments. Finding out how different pricing tactics, product modifications, and service quality affect